The Infancy and Childhood of Organizational Theory - Hodgson, Richard (Relations industrielles / Industrial Relations, 1967)
In the following article, the author tries, first, to make the point on the major contributions on organizational theory. He explains, after that, why he thinks this is still in about the stage of infancy, by underlining the need for a new spirit towards all those theories, where they may be going and what perhaps they will be able to do for us in the not-too-distant future.